Enhancing global and regional mechanisms for conflict management and resolution - Ibrahim A. Gambari (2014)
In this paper I provide an overview of the global perspectives on conflict management and conflict resolution and the international and regional efforts to address them. In this regard, I begin with some general and theoretical observations followed by a synopsis of three case studies (Cyprus, Darfur/Sudan and Myanmar), each one chosen from three regions (Europe, Africa and Asia) and based on my direct involvement in helping to resolve them. I then make some concluding remarks and recommendations on enhancing the mechanisms for conflict management and resolution.